Corporate Leverage and the Dynamics of Its Components - Hovakimian, Armen; Hovakimian, Gayané (Journal of Financial and Quantitative Analysis, 2021)
Abstract We investigate the dynamics of observed and target leverage ratios and deviations from the targets. The cross-sectional persistence in leverage ratios is driven by persistent targets, whereas time-series variation is driven by transitory deviations from targets. Consistent with dynamic trade-off theories, persistence is higher when the costs of deviating from targets are lower and when the adjustment costs are higher. Deviations are less persistent for firms that are over-levered and firms that are smaller, younger, or more focused or that have lower credit ratings. In recessions, excess leverage is less persistent for larger firms and is more persistent for smaller firms.